2021
DOI: 10.1136/bmjgh-2021-005883
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and operating a ‘virtual ward’ system to provide care for patients with COVID-19 at home: experience from The Gambia

Abstract: Health systems in sub-Saharan Africa have remained overstretched from dealing with endemic diseases, which limit their capacity to absorb additional stress from new and emerging infectious diseases. Against this backdrop, the rapidly evolving COVID-19 pandemic presented an additional challenge of insufficient hospital beds and human resource for health needed to deliver hospital-based COVID-19 care. Emerging evidence from high-income countries suggests that a ‘virtual ward’ (VW) system can provide adequate hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…[ 45 ] states that telemedicine has been used for teleconsultation with COVID-19 patients with mild symptoms. Teleconsultation service has been prominently utilized in various countries in sub-Saharan countries such as Botswana [ 31 ], Gambia [ 25 ], Uganda, Kenya, Ethiopia [ 39 ], Cameroon [ 44 ] and South Africa.
Fig.
…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 45 ] states that telemedicine has been used for teleconsultation with COVID-19 patients with mild symptoms. Teleconsultation service has been prominently utilized in various countries in sub-Saharan countries such as Botswana [ 31 ], Gambia [ 25 ], Uganda, Kenya, Ethiopia [ 39 ], Cameroon [ 44 ] and South Africa.
Fig.
…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The Internet is also a central part of virtual healthcare. However, most resource-constrained settings cannot afford the requirements of setting up a virtual healthcare system, which impedes the adoption and success of virtual care in Africa [ 25 ]. Even when the initial funding is available, it may not always be available to sustain such virtual healthcare systems.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In Gambia, in 2020, patients with confirmed COVID-19 and who quality for virtual care were assigned a physician with a digital thermometer to monitor daily axillary temperature. A virtual plan monitor plan was performed by the physicians relied on mobile telephones and messaging applications such as WhatsApp [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously shown that many children are vaccinated outside of the recommended time frames,32 especially in districts in the eastern part of the country 24. The first confirmed case of COVID-19 in The Gambia was identified on 17 March 2020 33. The evolution of the pandemic and measures taken to control the spread of COVID-19 in The Gambia have been previously described 34.…”
Section: Methodsmentioning
confidence: 99%
“… 24 The first confirmed case of COVID-19 in The Gambia was identified on 17 March 2020. 33 The evolution of the pandemic and measures taken to control the spread of COVID-19 in The Gambia have been previously described. 34 In brief, in the days following the confirmation of the first case, the government swiftly implemented a series of measures to curb further transmission.…”
Section: Methodsmentioning
confidence: 99%